Water Management through Canal Blocking to Improving Rice Productivity in Langsat Permai Village, Bunga Raya District, Siak Regency, Riau Province - Dini, Isna Rahma; Hapsoh; Wawan; Ranuda, Rendika; Suci Rahmayuni (Talenta Publisher Universitas Sumatera Utara, 2018)
The low productivity of paddy in Langsat Permai Village, Bunga Raya District, Siak Regency, one of them is causes the unavailability of sufficient water for crop cultivation, so it is necessary to do water management by making canal blocking to be used on rice plants in the area. This is done to meet the water needs of rice plants during the dry season. Therefore, assistance is provided through water management in Langsat Permai Village, Bunga Raya District, Siak Regency. Mentoring strategies are carried out by discussing directly with farmer groups about the impact of making canal blocking. Through this activity, the availability of water for rice plants during the dry season is fulfilled. Production of 1 Ha of rice before the blocking canal produced 4-5 tons/harvest to 6-7.8 tons/harvest after the canal blocking.